At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Let's solve the expression step-by-step:
[tex]\[ E = \sqrt[3]{\left[\left(\frac{1}{3}\right)^2 + \left(\frac{3}{2}\right)^{-2}\right]^{-1} - \left(1 \frac{1}{4}\right)^{-1}} \][/tex]
1. Calculate [tex]\(\left(\frac{1}{3}\right)^2\)[/tex]:
[tex]\[ \left(\frac{1}{3}\right)^2 = \frac{1}{9} \approx 0.1111 \][/tex]
2. Calculate [tex]\(\left(\frac{3}{2}\right)^{-2}\)[/tex]:
[tex]\[ \left(\frac{3}{2}\right)^{-2} = \left(\frac{2}{3}\right)^{2} = \frac{4}{9} \approx 0.4444 \][/tex]
3. Add the results of step 1 and step 2:
[tex]\[ \left(\frac{1}{3}\right)^2 + \left(\frac{3}{2}\right)^{-2} = \frac{1}{9} + \frac{4}{9} = \frac{5}{9} \approx 0.5556 \][/tex]
4. Take the inverse of this inner sum:
[tex]\[ \left(\frac{5}{9}\right)^{-1} = \frac{9}{5} \approx 1.8 \][/tex]
5. Convert the mixed fraction [tex]\(\left(1 \frac{1}{4}\right)\)[/tex] to an improper fraction:
[tex]\[ 1 \frac{1}{4} = 1 + \frac{1}{4} = \frac{5}{4} = 1.25 \][/tex]
6. Invert this improper fraction:
[tex]\[ \left(\frac{5}{4}\right)^{-1} = \frac{4}{5} = 0.8 \][/tex]
7. Subtract the result of step 6 from the result of step 4:
[tex]\[ 1.8 - 0.8 = 1.0 \][/tex]
8. Finally, take the cube root of the result from step 7:
[tex]\[ \sqrt[3]{1.0} = 1.0 \][/tex]
Thus, the value of [tex]\(E\)[/tex] is:
[tex]\[ E = 1.0 \][/tex]
[tex]\[ E = \sqrt[3]{\left[\left(\frac{1}{3}\right)^2 + \left(\frac{3}{2}\right)^{-2}\right]^{-1} - \left(1 \frac{1}{4}\right)^{-1}} \][/tex]
1. Calculate [tex]\(\left(\frac{1}{3}\right)^2\)[/tex]:
[tex]\[ \left(\frac{1}{3}\right)^2 = \frac{1}{9} \approx 0.1111 \][/tex]
2. Calculate [tex]\(\left(\frac{3}{2}\right)^{-2}\)[/tex]:
[tex]\[ \left(\frac{3}{2}\right)^{-2} = \left(\frac{2}{3}\right)^{2} = \frac{4}{9} \approx 0.4444 \][/tex]
3. Add the results of step 1 and step 2:
[tex]\[ \left(\frac{1}{3}\right)^2 + \left(\frac{3}{2}\right)^{-2} = \frac{1}{9} + \frac{4}{9} = \frac{5}{9} \approx 0.5556 \][/tex]
4. Take the inverse of this inner sum:
[tex]\[ \left(\frac{5}{9}\right)^{-1} = \frac{9}{5} \approx 1.8 \][/tex]
5. Convert the mixed fraction [tex]\(\left(1 \frac{1}{4}\right)\)[/tex] to an improper fraction:
[tex]\[ 1 \frac{1}{4} = 1 + \frac{1}{4} = \frac{5}{4} = 1.25 \][/tex]
6. Invert this improper fraction:
[tex]\[ \left(\frac{5}{4}\right)^{-1} = \frac{4}{5} = 0.8 \][/tex]
7. Subtract the result of step 6 from the result of step 4:
[tex]\[ 1.8 - 0.8 = 1.0 \][/tex]
8. Finally, take the cube root of the result from step 7:
[tex]\[ \sqrt[3]{1.0} = 1.0 \][/tex]
Thus, the value of [tex]\(E\)[/tex] is:
[tex]\[ E = 1.0 \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.